The application of green elements in bungalow residential projects / Sofia Nabilah Mohamad Zahid, Maisarah Makmor and Nor Azmi Ahmad Bari - Mohamad Zahid, Sofia Nabilah; Makmor, Maisarah; Ahmad Bari, Nor Azmi (UiTM Press, 2024)
Energy usage is the main culprit in multiple environmental problems. Usage of energy in residential sectors has contributed significantly to the primary energy consumption. Almost one million metric tonnes of carbon dioxide (CO2) can be reduced by applying green building elements in constructing, operating, and designing residential structures. Integrating green building elements as sustainable strategies can help to consume less energy and water while lowering carbon emissions. Extensive application of green building elements can uplift the detrimental impacts of development towards the environment. Thus, this study aims to investigate the green building elements suitable for bungalow residential projects in Malaysia. The achieve the aim of this study, three (3) objectives are utilised which are to identify green elements appropriate for residential bungalow developments, to determine green elements that work best for bungalow projects, and to analyse the barriers in applying the green elements in bungalow residential projects. The method for data collection administered in this study is semi-structured interviews with property developers that have involved in bungalow residential projects. The data collected has highlighted green building elements such as energy efficiency, waste management, and indoor environmental quality as crucial foundations for environmentally responsible and sustainable designs. The combination of these elements is necessary and effective to reduce energy usage and CO2 emissions for bungalow residential building projects.